Melittin-Based Nano-Delivery Systems for Cancer Therapy - Anqi Wang; Yuan Zheng; Wanxin Zhu; Liuxin Yang; Yang Yang; Jinliang Peng (Biomolecules, 2022)
Melittin (MEL) is a 26-amino acid polypeptide with a variety of pharmacological and toxicological effects, which include strong surface activity on cell lipid membranes, hemolytic activity, and potential anti-tumor properties. However, the clinical application of melittin is restricted due to its severe hemolytic activity. Different nanocarrier systems have been developed to achieve stable loading, side effects shielding, and tumor-targeted delivery, such as liposomes, cationic polymers, lipodisks, etc. In addition, MEL can be modified on nano drugs as a non-selective cytolytic peptide to enhance cellular uptake and endosomal/lysosomal escape. In this review, we discuss recent advances in MEL’s nano-delivery systems and MEL-modified nano drug carriers for cancer therapy.